Prevalence of sexual dysfunction among prenatal women attending the Greater Accra Regional Hospital, Ghana. Issue 1 (13th August 2020) - Maya, Ernest T.; Boamah, Martin O.; Agyabeng, Kofi; Srofenyoh, Emmanuel; Mumuni, Kareem; Samba, Ali
Abstract: Objective: To estimate the prevalence and types of sexual dysfunction in pregnancy. Methods: A cross‐sectional facility‐based descriptive study among pregnant women attending the prenatal clinic of the Greater Accra Regional Hospital, a large tertiary health facility in Accra, Ghana, from May to June 2018. The inclusion criteria were 18 years or older, singleton pregnancy of 8 gestational weeks or more, and residing with their partner for at least 4 weeks before the study. Face‐to‐face interviews were conducted among consecutively enrolled women by using the Female Sexual Function Index (FSFI) tool. Results: Overall, 425 women were enrolled. The mean age was 30.8 ± 4.8 years. The mean gestational age was 32.3 ± 7.1weeks (range 9.7–42.0 weeks). The prevalence of sexual dysfunction in pregnancy was 64.9% (95% confidence interval [CI], 60.3%–69.4%) but only 32 (7.5%) women self‐reported sexual problems. The predominant types of sexual disorder were desire disorder (377 [88.7%; 95% CI, 85.3%–91.4%] women) and arousal disorder (320 [75.3%; 95% CI, 71.0%–79.2%]). Conclusion: Sexual dysfunction in pregnancy was found to be common, but most pregnant women were not aware that they had it. Abstract : Sexual dysfunction in pregnancy was found to be prevalent in the study population in Ghana. The most common types were desire and arousal disorders.